Assessment of Rural Livelihood Options through JEEViKA in Siwan District of Bihar - Sharma, Dhiraj Kumar; Singh, Suman (National Geographical Journal of India, 2022)
Livelihood is the important concern for all living beings and livelihood options are primarily agriculture and allied occupations in the rural area. The Government's key strategy to rural development is to focus on rural livelihood programmes. The primegoals of these programmes have been to improve the quality of life of rural people by alleviating poverty, providingselfemployment and community infrastructure facilities.Bihar is one of the most populated state in India with 8.6 % of the country's population but covers only 2.8 % area of the country. JEEViKA is anambitious Bihar Rural Livelihood Project (BRLP). It has been designed to address rural poverty through collaboration of Bihar Government and theWorld Bank. According to annual report ofJEEViKA 2016-17, 19 lakhhouseholdsare directly involved in 534 different blocks of 38 districts of Bihar. The objective of the study is to analyse the role, structure and rural livelihood options through JEEViKAin Siwan district.This paper is based on secondary sources of data and field observation applyingqualitative analysis for interpretation.Secondary data have been collected from various government and non-governmentagencies. Maps are prepared in ArcGIS,and the data have been calculated in Excel.